IMPLEMENTASI PERATURAN GUBERNUR JAWA TIMUR NO. 50 TAHUN 2022 TENTANG PENANGGULANGAN PENYAKIT TUBERKULOSIS DI PUSKESMAS BADEGAN KABUPATEN PONOROGO - Joko Handoko, Sayudi; Pramono, Joko; Haryanto, Aris Tri (JI@P, 2024)
The purpose of this research is to determine the implementation of East Java Governor Regulation No. 50 of 2022 concerning the Management of Tuberculosis at the Badegan Public Health Center Ponorogo. This type of research is descriptive, carried out at the Badegan Public Health Center Ponorogo. Informants were selected used purposive sampling techniques. Data collection techniques used interviews, documentation and observation. The data analysis technique used qualitative data analysis. The research results show that communication between parties related to the implementation of the East Java Gubernatorial Regulation No. 50 of 2022 concerning the Management of Tuberculosis at the Badegan Public Health Center has been going well through outreach. Human resources are good, the budget is met and the facilities and infrastructure are complete, although distribution is sometimes late. The disposition between the parties has gone well because they have knowledge and understanding, the attitude of the implementer who accepts duties and responsibilities and high commitment accompanied by an honest and responsible attitude in carrying out their work. The bureaucratic structure functions according to its duties, is able to understand the tasks well and carry out according to the standart operaciona procedure. Obstacles in implementation are delays in facilities and infrastructure as well as patients taking medication, so efforts are needed to maintain drug stocks and continue to be intensive in increasing the duties of medication supervisor who come from patient families to continue to provide understanding to patients. Keywords: Implementation, Disease Management, Tuberculosis